2018
DOI: 10.26635/phd.2018.913
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and overcoming barriers to healthier lives

Abstract: Understanding the key determinants of health from a community perspective is essential to address and improve the health and wellbeing of its members.  This qualitative study aimed to explore and better understand New Zealand-based Pasifika communities’ sociocultural experiences and knowledge of health and wellbeing. Fifty-seven participants were involved in six separate focus groups. Community coordinators co-facilitated and transcribed the discussions and conducted thematic analysis. The findings suggested t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The most popular BCT was instruction on how to perform a behaviour (4.1), used to demonstrate culturally appropriate meals, facilitate exercise classes and provide educational sessions around the targeted health conditions and behaviours; followed by social support (unspecified) (3.1). Providing social support resonates with Pacific values, drawing strength from socio-cultural relationships within their collective contexts, such as extended family, community, and church networks [17,22,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most popular BCT was instruction on how to perform a behaviour (4.1), used to demonstrate culturally appropriate meals, facilitate exercise classes and provide educational sessions around the targeted health conditions and behaviours; followed by social support (unspecified) (3.1). Providing social support resonates with Pacific values, drawing strength from socio-cultural relationships within their collective contexts, such as extended family, community, and church networks [17,22,28].…”
Section: Discussionmentioning
confidence: 99%
“…An individual's motivation to change behaviour is strongly interwoven with the socio-cultural roles and family responsibilities [20,[25][26][27]. Several studies have highlighted Pacific people to perceive health as being able to provide for their families and the wellbeing of their family unit, rather than the physical ailments of an individual [21,28,29]. Moreover, studies that have included family and social support have shown to be more effective than those requiring individuals to undertake behaviour change on their own accord [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Co-design methods were used to understand the needs and aspirations of Māori and Pasifika communities. 15,16 Models of health and wellbeing that were specific to Māori and Pasifika peoples 17,18 were used to interpret focus group findings, and an mHealth tool was co-designed with these focus groups, that incorporated relevant content and features that aligned with the needs and wants of these communities. The theoretical domains framework 19 and behaviour change taxonomy 20 were then used to identify evidence-based behavioural determinants and behavioural change techniques that aligned with and could be incorporated into the content and features of the OL@-OR@ programme.…”
Section: Introductionmentioning
confidence: 99%